Atom probe Tomography of fast-diffusing impurities and the effect of gettering in multicrystalline silicon - Tweddle, D; Shaw, E; Douglas, J; Bonilla, R; Moody, M; Hamer, P; Wilshaw, P (AIP Publishing, 2018)
This article demonstrates an approach for multiscale characterisation of individual defects, such as grain boundaries, in multicrystalline silicon. The analysis techniques range from macroscale characterisation of average bulk lifetime, through photoluminescence to resolve spatial recombination, and finally to nanoscale analysis of the crystallographic characteristics and impurity decoration of the grain boundary using Transmission Kikuchi Diffraction and Atom Probe Tomography. This method can be used to characterise defects and their response to processing, such as gettering and hydrogen passivation. In this paper it is applied to the test case of Saw Damage Gettering on Red Zone High Performance Multicrystalline Silicon. In both as-cast and gettered samples, copper and chromium were observed at a recombination active, random angle grain boundary. After gettering the copper excess was found to decrease. In contrast, the slower diffusing chromium was found to increase, potentially indicating internal gettering. At a recombination inactive Σ3 grain boundary only oxygen was observed at the boundary before gettering, with no transition metals detected.